Effects of GnRHa on plasma sex steroid hormones of river catfish Hemibagrus nemurus (Valenciennes 1840) - Adebiyi, Fatimat Adenike; Siraj, Siti Shapor; Harmin, Sharr Azni; Christianus, Annie (Penerbit Universiti Kebangsaan Malaysia, 2013)
The effect of gonadotropin releasing hormone analogue (GnRHa) on plasma sex steroid hormones of river catfish Hemibagrus nemurus was studied. Enzyme linked immunosorbent assay (ELISA) was used to measure the hormones. The fish were treated with saline (control) and GnRHa at various doses of 5 µg/kg, 20 µg/kg and 50 µg/kg body weight (BW) of fish. Blood samples were collected at 0, 6, 12 and 24 h post hormone administration. The results showed that GnRHa elevated the plasma sex steroid hormones even at a low dose of 5 µg/kg. Significant increase (p< 0.05) in plasma sex steroid levels were observed with 20 µg/kg and 50 µg/kg BW GnRHa treatments and a dose of 5 µg/kg BW GnRHa produced a slow response to steroidogenesis. Treatment with 50 µg/kg BW GnRHa produced the best result. The highest level of testosterone, 11-ketotestosterone and 17β-estradiol were observed at 24 h for all treatments. The results indicated that GnRHa increased steroid production in the plasma of H. nemurus. Therefore, it can be used as an inducing agent for the control of reproduction in H. nemurus.